2018
DOI: 10.1098/rsos.181411
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical characterization of high-rank coal by nuclear magnetic resonance: a case study of the Baijiao coal reservoir, SW China

Abstract: To better apply nuclear magnetic resonance (NMR) to evaluate the petrophysical characterization of high-rank coal, six anthracite samples from the Baijiao coal reservoir were measured by NMR. The porosity, T2 cutoff value, permeability and pore type were analysed using the transverse relaxation time (T2) spectrum before and after centrifugation. The results show that the T2 spectrum of water-saturated anthracite can be divided into a discontinuous and continuous trimodal distribution. According to the connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…While Tang et al [7] experimentally studied the effect of temperature on spontaneous combustion of coal and proposed the critical temperature for spontaneous combustion of different coal types. Several researchers found that gas adsorption in coal is related to the oxygen functional group by infrared spectroscopy, and the oxygen concentration affects the combustion of coal particles [8][9][10][11]. Recently, Xin et al [12,13] carried out continuous measurement on sub-bituminous coal samples under different temperatures and oxygen concentrations, and analysed the chemical relationship between oxygen consumption and oxygen effect.…”
Section: Introductionmentioning
confidence: 99%
“…While Tang et al [7] experimentally studied the effect of temperature on spontaneous combustion of coal and proposed the critical temperature for spontaneous combustion of different coal types. Several researchers found that gas adsorption in coal is related to the oxygen functional group by infrared spectroscopy, and the oxygen concentration affects the combustion of coal particles [8][9][10][11]. Recently, Xin et al [12,13] carried out continuous measurement on sub-bituminous coal samples under different temperatures and oxygen concentrations, and analysed the chemical relationship between oxygen consumption and oxygen effect.…”
Section: Introductionmentioning
confidence: 99%
“…According to the principles of NMR, the total lateral relaxation rate 1T2 can be expressed as follows 31 : 1T2=1T2b+1T2s+1T2d, where T2b is the transverse relaxation time of free fluid, T2s is the transverse relaxation time of fluid caused by surface relaxation, and T2d is the transverse relaxation time caused by diffusion relaxation in a gradient magnetic field; surface relaxation plays a major role. Based on Equation 1, the T 2 spectrum obtained by NMR experiments can reflect the pore size distribution characteristics of sandstone samples treated at different temperatures.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Finally, the different samples were observed by a Quattro S scanning electron microscope system, and micromorphology photos of each sample were obtained. According to the principles of NMR, the total lateral relaxation rate 1 T 2 can be expressed as follows 31 :…”
Section: Sem Testmentioning
confidence: 99%
“…The critical value I HRC at the boundary between supercriticality and subcriticality was determined as a function of pile volume. (5) The effect of the ratio of coal particle size to coal pile size, D/L S , on T CSIT was incorporated into the original equation that gave T CSIT in terms of just coal pile volume. The modified equation may be useful to evaluate the effect of coal particle size on coal temperature rise in a coal pile.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the mining method, coal is transported to the ground in large quantities, and because of the intrinsic properties of coal, this presents hazards in all processing stages after mining [1]. These hazards include spontaneous combustion resulting from the complex physical and chemical structure of coal and its propensity to oxidization [2][3][4][5]. The spontaneous combustion of coal starts from slow physico-chemical reaction processes in the low-temperature range, culminating in a final stage when red-hot spots can be found on the surfaces of coal piles or pillars.…”
Section: Introductionmentioning
confidence: 99%